MARKET REACTION MODERATE MEDIA EXPOSURE AND PUBLIC OWNERSHIP TO SUSTAINABILITY REPORTS - Arini Nurul Pujiani; Iin Rosini; Nofryanti (ZILLZELL MEDIA PRIMA, 2024)
This research aims to test market reactions moderating media exposure and public ownership of sustainability reports in companies in the energy sector and industrial sector during the 2021 - 2022 period. This research is classified as associative quantitative research. The data used is secondary data obtained from the website www.idx.co.id and the company website. The population in this research are companies in the energy sector and industrial sector on the stock exchange during the period 2021 to 2022. Meanwhile, the sample for this research was determined using a purposive sampling method so that 62 sample companies were obtained. By using panel data regression analysis with a random effect model, this research finds that media exposure has no effect on sustainability reports, public ownership has no effect on sustainability reports. This research also found that market reactions cannot moderate the influence of media exposure on sustainability reports, market reactions cannot moderate the influence of public ownership on sustainability reports. This research contributes to the literature regarding the use of random effect panel regression methods, which has not been widely found in the Indonesian research context. This research has implications for the importance of more transparent and detailed sustainability reports that can demonstrate a company's long-term commitment to sustainable business practices. Meanwhile, for further research, it is hoped that other independent variables such as financial performance and company culture can be used to influence sustainability report disclosure.